2020
DOI: 10.14295/bds.2020.v23i1.1800
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin-A injections as therapy for chronic painful post-traumatic trigeminal neuropathy: case report

Abstract: Painful post-traumatic trigeminal neuropathy (PTTN) involves spontaneous and evoked pain, of moderate to severe intensity, continuous and described as burning or shooting. The first line treatment is pharmacological. However, botulinum toxin - A (BoNT-A) can be used when medications cannot control pain. This article describes the use of BoNT-A in a case of PTTN refractory to conventional pharmacological treatment. A 44-year-old male patient presented with an 8-years history of pain in the lower left se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…Another relatively recent suggestion for the control of peripheral neuropathic pain is the use of local botulinum toxin, serotype A (BoNT‐A). Injections at the painful site with BoNT‐A seem to be effective in reducing PTNP 105,106 . A multicentre study has shown that that the presence or intensity of allodynia at baseline was associated with a significantly stronger response to the repeated administration of BoNT‐A in patients with multi‐aetiology peripheral neuropathic pain 107 .…”
Section: Ptnp Prevention and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relatively recent suggestion for the control of peripheral neuropathic pain is the use of local botulinum toxin, serotype A (BoNT‐A). Injections at the painful site with BoNT‐A seem to be effective in reducing PTNP 105,106 . A multicentre study has shown that that the presence or intensity of allodynia at baseline was associated with a significantly stronger response to the repeated administration of BoNT‐A in patients with multi‐aetiology peripheral neuropathic pain 107 .…”
Section: Ptnp Prevention and Managementmentioning
confidence: 99%
“…Injections at the painful site with BoNT-A seem to be effective in reducing PTNP. 105,106 A multicentre study has shown that that the presence or intensity of allodynia at baseline was associated with a significantly stronger response to the repeated administration of BoNT-A in patients with multi-aetiology peripheral neuropathic pain. 107 Animal studies also suggested that local injections of Recently the study of the endocannabinoid system, and its role in pain control, suggested that cannabinoids may play a role in managing chronic pain conditions.…”
Section: F I G U R Ementioning
confidence: 99%
“…Botulinum toxin (BTX) injection therapy can help control PTTN pain when existing pharmacological treatments are ineffective [37,38]. BTX inhibits the release of various nociceptive mediators such as substance P, glutamate, and Calcitonin Gene-Related Peptide (CGRP) and expresses TRPV1, justifying its use in peripheral neuropathic pain [37,38].…”
Section: Considerations For the Treatment Of Pttnmentioning
confidence: 99%
“…Various administration protocols for botulinum toxin in treating neuropathic pain have been reported, but there is no consensus on the optimal dosage for achieving an adequate therapeutic effect [37][38][39]. A recent systematic review reported that 25 to 100 units for trigeminal neuralgia are administered divided into 1 to 20 injections [37].…”
Section: Considerations For the Treatment Of Pttnmentioning
confidence: 99%
“…A necessidade de reaplicação periódica da toxina consiste em um fator limitante para continuidade do tratamento. CANALES et al (2020) observou redução da intensidade da dor em casos de neuropatia trigeminal póstraumática após injeção de TxB-A como agente terapêutico, sendo aplicada com base na região dolorosa, sem haver combinação de tratamentos ou farmacoterapia convencional, apresentando resultados significativos entre a segunda semana e o terceiro mês de acompanhamento. Todavia, as desistências de alguns pacientes para as doses de reforço ocasionaram a administração de apenas uma dose, impossibilitando o acompanhamento dos resultados em longo prazo.…”
Section: Revisão De Literaturaunclassified